Midianites and the Children of Israel in the Qur’ān: The Missed Encounter at Horeb - Gobillot, Genevieve (Antiguo Oriente, 2026)
Although the Qurʾānic material concerning the history of Midian is dispersed across several suras, a close reading reveals a striking internal coherence. The Midianites occupy a pivotal role in this narrative, which unfolds in three interrelated stages. First, the Qurʾān implicitly abrogates the account of Midian’s annihilation by the Israelite army under Moses, as narrated in Numbers 31. This abrogation aligns with interpretive principles attested in the Pseudo-Clementine Writings, according to which neither God—understood as good and merciful—nor His messenger, could command the indiscriminate slaughter of women and children. Second, while rejecting the biblical depiction of total destruction, the Qurʾān nonetheless affirms that the Midianites, having committed repeated acts of injustice, deceit, and violence against the peoples with whom they traded, were subjected to a divine punishment during the Mosaic period. Qurʾānic terminology indicates that those guilty of wrongdoing perished as a result of a cataclysmic event, being swallowed up by fissures caused by an earthquake. Third, this ordeal is presented as coinciding with the bestowal of the Second Tablets of the Law, at the foot of a volcanic Horeb located on the Arabian Peninsula, within the framework of an encounter between the two messengers, Moses and his father-in-law Shuʿayb (the biblical Jethro). This meeting appears to have been intended to affirm a shared participation of the Arabs and the Children of Israel in the Abrahamic inheritance—an outcome ultimately thwarted by the Midianites’ rejection and rebellion against God.